2013
DOI: 10.1007/s13744-013-0144-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Insecticidal Potential of Eucalyptus urograndis Essential Oil Against Rhodnius neglectus Lent (Hemiptera: Reduviidae)

Abstract: The resistance of triatomines to pyrethroids has been reported in several Latin American countries, including Brazil, indicating the need for the development of new approaches for the control of vectors of the Chagas disease. In here, we evaluated the insecticidal potential of the essential oil of Eucalyptus urograndis (Myrtaceae) against unsexed third and fourth instars of Rhodnius neglectus Lent (Hemiptera: Reduviidae) in topical application, fumigation, surface contact, and repellency . The insecticidal act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…In addition, terpenes also affect components of the epicuticular waxes of insects, which could be a mechanism of pesticidal activity [79]. Repellent and ovicidal activities were also observed for different extracts from Schinus molle [80], and Eucalyptus urograndis essential oil had high insecticidal and repellent activities for R. neglectus nymphs [76,77]. DEET (N,N-diethyl-3-methylbenzamide) is a synthetic compound that is used as repellent against mosquitoes and other Diptera, with the repellency of DEET on the bug vectors of Chagas disease having been tested by other authors [78,81,82].…”
Section: Triatominae Bugs (Vector Of Chagas Disease)mentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, terpenes also affect components of the epicuticular waxes of insects, which could be a mechanism of pesticidal activity [79]. Repellent and ovicidal activities were also observed for different extracts from Schinus molle [80], and Eucalyptus urograndis essential oil had high insecticidal and repellent activities for R. neglectus nymphs [76,77]. DEET (N,N-diethyl-3-methylbenzamide) is a synthetic compound that is used as repellent against mosquitoes and other Diptera, with the repellency of DEET on the bug vectors of Chagas disease having been tested by other authors [78,81,82].…”
Section: Triatominae Bugs (Vector Of Chagas Disease)mentioning
confidence: 98%
“…Essential oils are an alternative to synthetic pesticides for controlling blood sucking bugs [43,[76][77][78], with Hedeoma mandoniana and Minthostachys andina having been used as insecticides on the bugs Rhodnius neglectus and Triatoma infestans, and topical application revealing an insecticidal activity of 33% and 50% for H. mandoniana and M. andina, respectively. However, the evaluation of these essential oils as a fumigant produced different results, with H. mandoniana oil combined with 25.5% menthone and 33% isomenthone showing a mortality between 30 and 50% for the bugs, while M. andina with pulegone as the main component (44.6%) had no effect.…”
Section: Triatominae Bugs (Vector Of Chagas Disease)mentioning
confidence: 99%
“…Sales et al (2017) reported that α-pinene and the minor compounds (β-pinene, terpinen-4-ol, p-cymene, y-terpinene, myrcene and linalool) present in the EO of Callistemon viminalis G. (Myrtaceae), were likely be responsible for repelling M. persicae from tomato leaf discs treated with this oil. Another species of the Myrtaceae family, Eucalyptus urograndis also showed repellent activity in its essential oil when tested against nymphs of Rhodnius neglectus (Hemiptera: Redu viidae) with 80% average repellency (Gomes and Favero 2013). The authors also observed a decrease in repellency after 24 h, inversely proportional to the time, due to oil evaporation.…”
Section: Discussionmentioning
confidence: 93%
“…These components are assumed to represent the plant constitutive defense mechanisms or could be a part of the allelopathic mechanisms. Eucalyptus volatile components are known for their insecticidal and larvicidal activities (Batish et al, 2008;Cheng et al, 2009;Alzogaray et al, 2011;Gomes and Favero, 2013). Unfortunately, almost all these studies concentrate on the effect of total fraction, not the individual components.…”
Section: Plant Defense and Allelopathymentioning
confidence: 99%